Służba Ochrony Państwa – nowa instytucja w systemie bezpieczeństwa RP .......... 11 - Sieklucki, Dominik (Systemy bezpieczeństwa: Wymiar lokalny i państwowy, 2020)
On February 1, 2018, the State Protection Service (SOP), an institution established in place of the Government Protection Bureau (BOR), has started operating. The aims of the paper are to indicate the most important reasons for establishing a new formation, identify the fundamental differences between BOR and SOP, and define the basic features of the State Protection Service as a state institution in terms of law and administration. The author’s intention is also to refer to the problem of the location of the SOP in the structure of the administration of order and security in Poland, both in the context of increasing the scope of its powers in relation to the BOR, justifying the thesis about a fundamental change in the position of this formation, which as a guard of a protective nature has gained an actual position making it similar to the group of intelligence (special) services.